Desempenho de cultivares de alface em sistema semi-hidropônico fertirrigadas com soluções nutritivas salinizadas - Dias, Rayssa Honório (Universidade Federal Rural do Semi-Árido, 2019)
Lettuce is a vegetable widely cultivated throughout the national territory due to its adaptability to different climatic conditions and easy handling and, due to the growing demand in food production, there is a need for new techniques aimed at increasing the productivity efficiency of crops. The aim of this research was to evaluate the performance and quality of crisp lettuce cultivars grown in semi-hydroponic system using salt nutrient solutions. The experiment was carried out in a randomized complete block design with five levels of nutrient solution salinity (1.8, 2.8, 3.8, 5.8 dS m-1) and four lettuce cultivars (Solaris, Betânia, Elba and Mimosa) with 3 replicates The plants were harvested 35 days after transplanting and the main growth morphological characteristics were evaluated: total number of leaves, number of commercial leaves, total fresh mass, commercial fresh mass, total dry mass, stem diameter, stem length, area foliar, specific leaf area and leaf succulence. In the absence of salt stress, the Betânia and Solaris varieties are more productive. The Mimosa cultivar did not adapt well to the cultivation conditions, presenting precocious tossing. The cultivar Elba is more tolerant while the cultivar Solaris is more sensitive to salinity.
Monografia
Keywords: Fibra de coco; Estresse salino; Fertirrigação; Salinidade; Coconut fiber; Saline stress; Fertigation; Salinity; CIENCIAS AGRARIAS::AGRONOMIA